Rethinking Food Processing for a Sustainable Future: A Review of Innovative Nonthermal Technologies - Chaudhary, Muneeba Naseer; Hussain, Mudassar; AL-Ansi, Waleed; Luo, Wei (International Journal of Environment, Agriculture and Biotechnology, 2024)
Agricultural innovation offers a solution to mounting pressures on the global food system, which must provide safe, nutritious, and environmentally sustainable consumable goods at increasing volumes if demands are to be met. The potential of nonthermal technologies as promising alternatives to conventional thermal treatments for sustainable food processing and preservation is discussed in this review. Here we investigate four of such emerging nonthermal technologies that include High-Pressure Processing (HPP), Pulsed Electric Fields (PEF) and Irradiation, and Cold Plasma. This blog takes a deeper dive into its principles, use cases, and pros and cons. On the other hand, nonthermal technologies are energy-sparing, improve the nutritional quality of food products, and reduce loss due to processing but above all provide improved environmental performance. The energy-saving potential of these technologies can be large, while maintaining food in its original nutritive and sensory shape but with extended shelf life and lower carbon footprint. Nevertheless, scalability, cost-efficacy regulatory approval, consumer acceptance (Diaz-Ruiz Pletsch Concordet; Chellaram Barragan Maheswari), integration with the reference’s infrastructure, or optimized process parameters are themselves challenging. Developing a solution to these challenges and promoting nonthermal processing technologies are strategic priorities that will be critical for future food production... With time, advances in research and developments of this important field would give rise to the wide-scale application of nonthermal processing This review aims to provide a full overview of potential benefits entailed by each innovative technique along with its limitations as well as informing stakeholders and future directions.